Blood in their eyes : the Elaine Massacre of 1919 - Stockley, Grif; Mitchell, Brian K.; Lancaster, Guy, 1976- (Fayetteville : The University of Arkansas Press, 2020)
"The second edition of the authoritative text on the Elaine Massacre which took place in Elaine, Arkansas in 1919. With contributions by fellow historians Brian K. Mitchell and Guy Lancaster, this second edition of Blood in Their Eyes draws from recently discovered sources to explore in greater detail the actions of the mob and the lives of those who survived the massacre"--
Introduction to the Revised Edition -- Introduction to the First Edition -- Ch. 1. Charles Hillman Brough's midnight train ride -- ch. 2. The law of the delta -- ch. 3. The boys from Camp Pike -- ch. 4. A committee of seven -- ch. 5. More than one version -- ch. 6. Little Rock and New York : an uneasy alliance -- ch. 7. The trials begin -- ch. 8. Colonel Murphy for the defense -- ch. 9. The retrials of the Ware defendants -- ch. 10. The changing of the guard -- ch. 11. Affidavits from unlikely sources -- ch. 12. Moore v. Dempsey : a supreme victory -- ch. 13. Scipio Jones takes charge -- Conclusion. On the larger meaning of Elaine.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 21, 2020).
JSTOR
Keywords: United States. -- Army -- Civic action -- History -- 20th century; United States. -- Army; Riots -- Arkansas -- Elaine -- History -- 20th century; Massacres -- Arkansas -- Elaine -- History -- 20th century; Sharecroppers -- Arkansas -- Phillips County -- Social conditions -- 20th century; African Americans -- Arkansas -- Phillips County -- Social conditions -- 20th century; African Americans -- Legal status, laws, etc. -- Arkansas -- Phillips County -- History -- 20th century; Trials (Murder) -- Arkansas -- Phillips County -- History -- 20th century; Elaine Massacre, Elaine, Ark., 1919.; Phillips County (Ark.) -- Race relations; Elaine (Ark.) -- Race relations; Camp Pike (Ark.) -- History -- 20th century; Métayers -- Arkansas -- Phillips -- Conditions sociales -- 20e siècle.; Noirs américains -- Arkansas -- Phillips -- Conditions sociales -- 20e siècle.; Procès (Meurtre) -- Arkansas -- Phillips -- Histoire -- 20e siècle.; SOCIAL SCIENCE / General; African Americans -- Legal status, laws, etc; African Americans -- Social conditions; Armed Forces -- Civic action; Massacres; Race relations; Riots; Trials (Murder); Arkansas -- Camp Joseph T. Robinson; Arkansas -- Elaine; Arkansas -- Phillips County; Legal status; 1900-1999; Electronic books; History